1977
DOI: 10.1111/j.1151-2916.1977.tb15479.x
|View full text |Cite
|
Sign up to set email alerts
|

Preparation, Characterization, and Properties of Dy‐Doped Small‐Grained BaTiO3 Ceramics

Abstract: The effects of Dy doping and sintering parameters on the properties of BaTiO3 ceramics were studied. The average grain size decreases with increasing Dy content and is controlled at ∼1.5 μ m by 0.8 at.% Dy. The Curie temperature change, associated with ≤1.2 at.% Dy, is <3°C. The dielectric constant is ∼2600 for specimens doped with 0.8 at.% Dy, calcined at 1200°C, and sintered at 1450°C. The dielectric constant variation with ambient temperature is much less than that of conventional BaTiO3 ceramics. Lattice c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
32
1

Year Published

1977
1977
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 144 publications
(42 citation statements)
references
References 12 publications
4
32
1
Order By: Relevance
“…Nb205 in that it decreased the axial ratio (c/a ratio) of the tetragonal phase. A similar reduction in tetragonality (c/a ratio) has been observed with rare earth metal oxide addition [2,14] to BaTiO3.…”
Section: Introductionmentioning
confidence: 52%
“…Nb205 in that it decreased the axial ratio (c/a ratio) of the tetragonal phase. A similar reduction in tetragonality (c/a ratio) has been observed with rare earth metal oxide addition [2,14] to BaTiO3.…”
Section: Introductionmentioning
confidence: 52%
“…We have utilized the Clabaugh method (20) using BaCl 2 и 2H 2 O, TiCl 4 , and C 2 O 4 и 2H 2 O (Merck pro analysis) the discovery of its extremely high dielectric constant. It is well known that the small particle size of BaTiO 3 starting as starting materials.…”
Section: Preparation Of the Batio 3 Samplesmentioning
confidence: 99%
“…Some La-doped PZT (or PLZT) compositions were found to produce ceramics with high density and good transparency which make them suitable for electro-optic applications [1]. For non-lead electroceramics, Yamaji et al [2] have investigated the effect of doping Dy 2 O 3 in BaTiO 3 and found that the average grain sizes of doped ceramics were smaller while the dielectric constants were greater than those of undoped BaTiO 3 over a wide range of temperature.…”
Section: Introductionmentioning
confidence: 98%